Detection of Fetal Corpus Callosum Abnormalities by Means of 3D Ultrasound - Pashaj, S.; Merz, E. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: The objective of this study was to prenatally detect corpus callosum pathologies such as agenesis, partial agenesis, hypo- and hyperplasia and enhanced echogenicity.Materials and Methods: Between 2009 and 2013 detailed 3D ultrasound examinations of the fetal corpus callosum were carried out as part of a level III examination for fetal anomalies. All scans were performed using Voluson E8 equipment (GE, Zipf, Austria) with a 5 – 8 MHz 3D transabdominal and 5 – 9 MHz 3D transvaginal transducer. All cases were evaluated for the following variables: inner, outer and curved length of the corpus callosum, height of the different segments of the corpus callosum and the corpus callosum area. All parameters were compared with normal growth charts. In all cases of suspected corpus callosum anomaly direct and indirect signs for corpus callosum agenesis and associated malformations were observed.Results: 31 fetuses with pathological corpus callosum were diagnosed with 3D ultrasound. Gestational age at the time of diagnosis ranged from 20 to 38 weeks. 12 cases showed agenesis, 11 cases partial agenesis, 5 cases hypoplasia, 2 cases a combination of partial hyper- and hypoplasia and one case a lipoma of the corpus callosum. In corpus callosum underdevelopment, the more affected parts were the body and splenium. Associated anomalies were present in 25 of the 31 cases (80.6%) of corpus callosum pathologies.Conclusion: 3D neurosonography serves as an excellent tool to precisely demonstrate the pathological development of the fetal corpus callosum. By correlating the measures with the function of each affected corpus callosum segment, we can try to get a vague prediction of the neurological prognosis.
Keywords: CNS; 3 D ultrasound; corpus callosum pathologies